THE ROLE OF STUDENTS IN MAINTAINING TRI HITA KARANA FOR EDUCATING YOUNG LEARNERS IN TRUNYAN VILLAGE, BANGLI (NARRATIVE STUDY OF STUDENTS COMMUNITY SERVICE) - yudyantara; I Wayan Lasmawan; Desak Putu Parmiti; Jayadiningrat, Made Gautama (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2025)
This study aimed at examining the role of students in community service in maintaining the Tri Hita Karana values for educating young learners in Trunyan Village, Bangli. Tri Hita Karana is described as 3 harmonious relations in human life consisting Parahyangan, Pawongan, and Palemahan. The study employed the qualitative research with narrative approach to retell the past experience or past events specifically the experience of students of community service in educating Tri Hita Karana to students in Kindergarten Prawidya Darma, Trunyan Village, Bangli. The data were collected to primary data by using the interview instrument. The setting of the research was in Trunyan Village, Bangli. The result showed that in Parahyangan, Pawongan, and Palemahan, the students of community service act as facilitator and example giver in educating students Tri Hita Karana values in Kindergarten Prawidya Darma. In Parahyangan Students of community service worship the God together with students in Kindergarten Prawidya Darma. In Pawongan, students of community service show respect and care when teaching the kindergarten students. In Palemahan, students of community service and kindergarten students clean up the Batur Lake and join a campaign of sorting rubbish. Thus, the implication of this study giving an insight about how to educate the values of Tri Hita Karana for kindergarten students in order to live in harmony and peace.